Faecal Calprotectin and Magnetic Resonance Enterography in Ileal Crohn's Disease: Correlations Between Disease Activity and Long-Term Follow-Up. (19th November 2018) - Jones, G R; Fascì-Spurio, F; Kennedy, N A; Plevris, N; Jenkinson, P; Lyons, M; Wong, L; MacLean, P; Glancy, S; Lees, C W
Abstract: Background and Aims: Magnetic resonance enterography [MRE] is the gold standard for assessing ileal inflammation in Crohn's disease [CD]. The aim of the present study was to correlate faecal calprotectin [FC] to MRE via a simple score in an exclusive ileal cohort with long-term follow-up for association with time to surgery or biologic therapy. Methods: In total, 150 MRE studies with matched FC [±30 days] were identified from the Edinburgh FC Register [2008–12; n = 18138]. Scans were re-read blinded to clinical data, independently, by two expert gastrointestinal radiologists, to generate a simple MRE score [range 0–10] from assessment of the worst intestinal segment plus total disease extent. Results: In total, 119 MRE scans were evaluated from 104 patients with ileal CD [L1 or L3 with panproctocolectomy]. Receiver operating characteristic analysis showed an area under the curve of 0.77 [0.67–0.87, p < 0.0001] for FC and MRE score >1, with an optimal cut-off of 145 μg/g for severe inflammation on MRE with 69.3% [57.6–79.5] sensitivity and 71.4% [53.7–85.4] specificity. Long-term follow-up over a median [interquartile range] of 2086 days [1786–2353] revealed FC ≥ 145 μg/g was associated with reduced biologic-free survival until 3 years following MRE, whereas MRE score [severe vs absent] was associated with reduced surgery- and biologic-free survival throughout follow-up. Backwards stepwise logistic regression revealed that length of ileal disease (odds ratio [OR] 3.8, 1.1–13.2, p = 0.034) and increased bowel wall thickness at MRE [OR 4.2, 1.6–10.7, p < 0.0001] or female sex [OR 5.2, 1.5–18.7, p = 0.011] increased the risk of biologic use or surgery, respectively. Conclusions: FC correlates well with MRE assessment of ileal CD with MRE parameters associated with long-term biologic- and surgery-free remission.